Shakespeare i Orijent / Shakespeare and the Orient: utjecaj šekspirijanske drame u Aziji - Khan, Shahab Yar (Context: Journal of Interdisciplinary Studies, 2022)
The history of drama in Asia is as old as the history of the world itself. In India however, according to the popular belief, the tradition of drama dates back to the prehistoric times. Due to this unique approach towards drama, that makes it a valuable divine gift for humanity, the esoteric significance of this art form has never seen decline in the cultural history of India. Drama, thus, acquires in Indian context a religious significance and represents as an art form the union of the celestial and the terrestrial. Drama (in Sanskrit Natak), in the Indian Subcontinent, has distinctive characteristic features. Essentially, as reflection of human existence, it is a combination of all the known art forms and, therefore, becomes the deepest expression of the human soul. The rise of Islamic culture and civilization in the twelfth and thirteenth centuries contributed to the amalgamation of the two great civilizations. The impact of the Muslim culture in transforming the classical features of Indian music, architecture, science, literature, etc. can by no means be undermined. By the end of the sixteenth century, the century of liberal humanism and coincidently the era of the rise of the Mughal Empire, the theatrical art had gained enormous significance in India. There is enough evidence to believe that Shakespeare’s plays were first performed in India during the reign of the Mughals (1526-1857). Later, the newly emerging colonial power, the English, in its first stronghold in India, Calcutta, established alongside other bureaucratic, political and educational institutions, the Garrison Theater. The earliest performances at this theater date back to 1770s and the first ever documented English play on the Indian soil happens to be Shakespeare’s Othello. Shakespeare’s unique dramatic structure smoothly found its place of prominence in the cultural life of India, offering new dimensions to the already existing rich local tradition and at the same time enriching its own dramatic expression. Today, all the major educational institutions of the Subcontinent cherish the tradition of mounting on stage the annual performances of Shakespeare’s plays and the cinematographic tradition has incorporated his works into its popular tradition from the very beginning of the history of the film industry in India.